Sensor Penyiaran Televisi Indonesia : Menyoal Muatan Negatif Dalam Konten Siaran Televisi - Novy Khusnul Khotimah; Dessy Kushardiyanti (Jurnal Mediakita : Jurnal Komunikasi dan Penyiaran Islam, 2022)
Censorship on television becomes a polemic in society, especially when censorship is carried out on certain images which even become controversial because they are considered unrealistic. Various parties regretted it, but not a few criticized and blamed the government in this case KPI and LSF for their ignorance of the censorship system on television. Although the issue of censorship is not the realm of the KPI in a pragmatic manner, it still has a big role to play in this situation because it governs the policy. How to make and apply laws and regulations when applied by television practitioners so that it gives rise to various interpretations including the irrelevant censorship. Analytical descriptive research method is used in reviewing this research by making an actual and factual path analysis regarding the facts, policies and implications of television broadcasting industry policies. The results of this study indicate that there is a need for intense supervision from KPI and LSF in their capacity to censor television station programs and anticipate the various censorship limits of television companies as a result of differences in human resources and technology capabilities and the application of censorship.